The use of emergency hormonal contraception in South Africa: current and future perspectives - N. Dahan-Farkas; M. Vally (South African Family Practice)
Emergency hormonal contraceptives play an important role in preventing unplanned pregnancies in South Africa. In this review, we discuss the levonorgestrel emergency contraceptive, the combined estrogen and progestin regimen (also known as the Yuzpe method) and the use of Ulipristal acetate. The levonorgestrel and the combined estrogen, progestin regimen are available in South Africa. The specific mechanisms of action of each of these emergency hormonal contraceptives will be discussed as well as their efficacy, the side effects associated with each of these preparations and the drug interactions. Levonorgestrel can be used as a single dose (1.5 mg) instead of two doses (0.75 mg) 12 hours apart. Levonorgestrel is very effective, with fewer adverse effects than the combined estrogen and progestogen administration. Levonorgestrel and the Yuzpe method have demonstrated good efficacy when utilised within 72 hours after unprotected intercourse or contraceptive failure. These emergency hormonal contraceptives should not be used as regular contraception. It is essential that all health professionals and educators inform women of reproductive age about the risks and common side effects of emergency hormonal contraceptives.